Digital Health Literacy Competencies of Students in Faculty of Health Science - Haikal Haikal; Enny Rachmani; Bayu Yoni Setyo Nugroho; Muhammad Iqbal; Jaka Prasetya; Syahifful Yudi Nugroho (Disease Prevention and Public Health Journal, 2023)
Background: Students are the most significant internet users in Indonesia. 49.52% of internet user groups in Indonesia are students. High internet users do not guarantee that digital health literacy is also high. Students at the Universitas Dian Nuswantoro health faculty are responsible for disseminating health information and transmitting digital health literacy interests. Health literacy skills are necessary for health students to sort out doubtful information. Good health literacy skills will impact students' ability to assess incoming data and make appropriate health decisions. This study aims to describe the digital health literacy skills possessed by students of the Faculty of Health. Universitas Dian Nuswantoro. Method: This descriptive study provides an overview/description of the digital health literacy skills possessed by students of the Faculty of Health. Universitas Dian Nuswantoro. The research population of health students is 1.642 people with the sample being 321 students. Data collection using Google Forms and distributed through class groups in WhatsApp (WA) and communicated privately. The statistical test used descriptive statistical analysis. Results: Faculty of Health Science at Universitas Dian Nuswantoro students had an "Advanced" or "Independent-Advanced" level of competence. The advanced level indicates that their digital competencies and health information skills are at their current status and without problems. Indicators that digital health literacy can improve our safety. Thus. students can improve methods for securing personal data. Conclusion: Digital health literacy is an ability needed in today's digital era. What needs to be improved is that students can choose the most appropriate method to protect personal data.